2013
DOI: 10.1111/cod.12053
|View full text |Cite
|
Sign up to set email alerts
|

Unexpected loss of contact allergy to aluminium induced by vaccine

Abstract: BackgroundIn studies in Gothenburg, Sweden, in the 1990s of an aluminium hydroxide-adsorbed pertussis toxoid vaccine, 745 of ∼76 000 vaccinated children developed long-lasting itchy subcutaneous nodules at the vaccination site. Of 495 children with itchy nodules patch tested for aluminium allergy, 376 (76%) were positive.ObjectivesTo study the prognosis of the vaccine-induced aluminium allergy.Patients and methodsTwo hundred and forty-one children with demonstrated aluminium allergy in the previous study were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
80
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(84 citation statements)
references
References 34 publications
3
80
0
1
Order By: Relevance
“…Five to 9 years after the initial tests, all children (352 + 25) with demonstrated aluminium allergy were offered a repeat patch test, which was performed in 2007‐2008. Of the 241 children tested a second time, in exactly the same way, 186 (77.2%) had negative test results . Type IV delayed hypersensitivity is generally considered to be lifelong, and such a large proportion becoming negative had never been described before .…”
Section: Introductionmentioning
confidence: 95%
“…Five to 9 years after the initial tests, all children (352 + 25) with demonstrated aluminium allergy were offered a repeat patch test, which was performed in 2007‐2008. Of the 241 children tested a second time, in exactly the same way, 186 (77.2%) had negative test results . Type IV delayed hypersensitivity is generally considered to be lifelong, and such a large proportion becoming negative had never been described before .…”
Section: Introductionmentioning
confidence: 95%
“…Children sensitized to aluminum may suffer contact dermatitis after exposure to objects that contain aluminum (eg, deodorants, toothpaste, or pigments used in tattooing) . However, some studies had showed that contact allergy to aluminum in children may wane or disappear with time, with negativization in up to 77% of children 7 years after the initial positive epicutaneous test …”
Section: Discussionmentioning
confidence: 99%
“…Before the early 2000s, only about 100 cases of persistent pruritic nodules after vaccination with aluminum‐absorbed vaccines had been reported . In addition to long‐lasting, pruritic nodules at the injection site, other commonly documented symptoms include excoriations, eczema, hyperpigmentation, hypopigmentation, hypertrichosis, and infiltration . These nodules have been reported to have several distinct histologic patterns, including subcutaneous collections of histiocytes, subcutaneous mononuclear inflammatory cell infiltrates with eosinophils and germinal center formation, and deep granuloma annulare–like infiltrates with surrounding dense collections of macrophages .…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that aluminum allergy in relation to childhood vaccines is temporary and frequently disappears years later . Most recently, a Swedish study retested patients with current or previous vaccine‐related pruritic nodules and found that 77% of retested children had negative patch tests 5–9 years after the initial positive patch test to aluminum …”
Section: Discussionmentioning
confidence: 99%